Microtransplantation in older patients with AML: A pilot study of safety, efficacy and immunologic effects. Issue 6 (30th March 2020) - Sung, Anthony D.; Jauhari, Shekeab; Siamakpour‐Reihani, Sharareh; Rao, Arati V.; Staats, Janet; Chan, Cliburn; Meyer, Everett; Gadi, Vijayakrishna K.; Nixon, Andrew B.; Lyu, Jing; Xie, Jichun; Bohannon, Lauren; et al.
Abstract: Older AML patients have low remission rates and poor survival outcomes with standard chemotherapy. Microtransplantation (MST) refers to infusion of allogeneic hematopoietic stem cells without substantial engraftment. MST has been shown to improve clinical outcomes compared with chemotherapy alone. This is the first trial reporting on broad correlative studies to define immunologic mechanisms of action of MST in older AML patients. Older patients with newly diagnosed AML were eligible for enrollment, receiving induction chemotherapy with cytarabine (100 mg/m2) on days 1‐7 and idarubicin (12 mg/m2) on days 1‐3 (7 + 3). MST was administered 24 hours later. Patients with complete response (CR) were eligible for consolidation with high dose cytarabine (HiDAC) and a second cycle of MST. Responses were evaluated according to standard criteria per NCCN. Immune correlative studies were performed. Sixteen patients were enrolled and received 7 + 3 and MST (median age 73 years). Nine (56%) had high‐risk and seven (44%) had standard‐risk cytogenetics. Ten episodes of CRS were observed. No cases of GVHD or treatment‐related mortality were reported. Event‐free survival (EFS) was 50% at 6 months and 19% at 1 year. Overall survival (OS) was 63% at 6 months and 44% at 1 year. Donor microchimerism was not detected. Longitudinal changes were noted in NGS, TCR sequencing, and cytokine assays. Addition of MST to induction and consolidation chemotherapy was well tolerated in older AML patients. Inferior survival outcomes in our study may be attributed to a higher proportion of very elderly patients with high‐risk features. Potential immunologic mechanisms of activity of MST include attenuation of inflammatory cytokines and emergence of tumor‐specific T cell clones.